The Effect of 7p (Product, Price, Place, Promotion People, Process, Physical Evidence) Marketing Mix and Patient Satisfaction on Outpatient Retention with the Role of Electronic Word of Mouth (E-WOM) Mediation at Bunda Margonda Hospital in 2025 - Alindra Maulidiya Mecca; Oci Etri Nursanty; Yuhelmis Yuhelmis (International Journal of Health and Pharmaceutical (IJHP), 2025)
Marketing mix is a set of strategies used by service organizations, including hospitals, to create value and influence consumer decisions through seven main elements, namely Product, Price, Place, Promotion, People, process, and physical evidence. In the context of healthcare, the implementation of an effective marketing mix is believed to be able to increase satisfaction and retain patients. This study aims to analyze the influence of marketing mix on outpatient retention with electronic word of mouth (e-WOM) as a mediating variable. The research method used is quantitative with a cross sectional approach. Sampling in this study used purposive sampling of 100 respondents. Data analysis was carried out using multiple linear regression as well as the Sobel test to test the influence of mediation. The results showed that Product, Price, Place, Promotion, People, process, physical evidence and patient satisfaction had a significant effect on patient retention with a sig value (0.000<0.05). The conclusion of this study is that there is an influence between the 7P marketing mix and patient satisfaction on outpatient retention with a value (sig 0.000<0.05), and there is no influence between Promotion, Place, and process on patient retention through e-WOM (sig >0.05).